STUDY OF CONSUMER ACCEPTANCE ON SHREDDED CARP (Osphronemus goramy) WITH BREADFRUIT (Artocarpus altilis)ADDITION - Zira Ielvia; Desmelati Desmelati; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was aimed to determine the effect of breadfruit(Artocarpus altilis)addition on shredded carp (Osphronemus goramy)to consumer acceptance. The method used was experimental with Completely Randomized Design (CRD) which consists of 4 treatment levels of addition various breadfruit concentrations on shredded carp: A0 (0%), A1 (20%), A2 (40%), A3 (60%). The parameters tested were organoleptic and proximate analysis.The results showed that the addition 20% of breadfruitin shredded carp was the best treatment and most preferable by consumer with 77 panelist (96.25%).The characteristics of golden yellow appearance, the typical aroma of fish still feels, the texture of coarse, soft and dryfibers, the savory taste still feels with medium flavor. The proximate analysis for water, protein, fat, ash, and fiber content was 1.06%, 24.92%, 18.24%, 3.78% and 0.93%, respectively.Keywords: breadfruit addition, chemical composition, consumer acceptance, shredded carp